The changing demographics of traumatic spinal cord injury: An 11-year study of 831 patients - Thompson, Cynthia (J Spinal Cord Med, 2015)
CONTEXT/OBJECTIVE: Traumatic spinal cord injuries (T-SCI) have a devastating impact and place a significant financial burden on the healthcare system. The incidence of T-SCI ranges from 10.4 to 83 cases per million and varies with age, sex, or geographical region. This study describes the epidemiology and demographic characteristics of patients treated for T-SCI in our region over 11 years. DESIGN: Retrospective cohort study. SETTING: Single Level-I trauma center in Québec, Canada. PARTICIPANTS: Patients who sustained T-SCI between 1 April 2000 and 31 March 2011. INTERVENTIONS: None. OUTCOME MEASURES: Data concerning T-SCI patients was retrieved from the Québec Trauma Registry. Information on age, sex, trauma, level of injury, type and severity of neurological deficit (ASIA scale), and treatment was extracted. Annual, age-standardized rates of T-SCI were calculated and trends over time were examined. RESULTS: Eight hundred and thirty-one patients with T-SCI were identified. The incidence of T-SCI did not change over time but there was a 13-year increase in age between 2002 and 2010. More than 60% of patients aged 55 years or more were injured following a fall and 80% became tetraplegic. These patients were more likely to have central cord syndrome (CCS) and incomplete neurological injury, compared to younger patients. The incidence of CCS increased from 25 to 37% over 11 years. CONCLUSIONS: The T-SCI population is aging and is more frequently sustaining injuries associated with CCS, incomplete neurological deficits and tetraplegia.